The Efficacy of Shareholder Voting: Evidence from Equity Compensation Plans - ARMSTRONG, CHRISTOPHER S.; GOW, IAN D.; LARCKER, DAVID F. (Journal of Accounting Research, 2013)
ABSTRACT This study examines the effects of shareholder support for equity compensation plans on subsequent CEO compensation. Using cross‐sectional regression, instrumental variable, and regression discontinuity research designs, we find little evidence that either lower shareholder voting support for, or outright rejection of, proposed equity compensation plans leads to decreases in the level or composition of future CEO incentive compensation. We also find that, in cases where the equity compensation plan is rejected by shareholders, firms are more likely to propose, and shareholders are more likely to approve, a plan the following year. Our results suggest that shareholder votes for equity pay plans have little substantive impact on firms’ incentive compensation policies. Thus, recent regulatory efforts aimed at strengthening shareholder voting rights, particularly in the context of executive compensation, may have limited effect on firms’ compensation policies.